Hepatic Induction of Fatty Acid Binding Protein 4 Plays a Pathogenic Role in Sepsis in Mice - Hu, Bingfang (Am J Pathol, 2017)
Sepsis is defined as the host's deleterious systemic inflammatory response to microbial infections. Herein, we report an essential role of the fatty acid binding protein 4 (FABP4; alias adipocyte protein 2 or aP2), a lipid-binding chaperone, in sepsis response. Bioinformatic analysis of the Gene Expression Omnibus data sets showed the level of FABP4 was higher in the nonsurvival sepsis patients' whole blood compared to the survival cohorts. The expression of Fabp4 was induced in a liver-specific manner in cecal ligation and puncture (CLP) and lipopolysaccharide treatment models of sepsis. The induction of Fabp4 may have played a pathogenic role, because ectopic expression of Fabp4 in the liver sensitized mice to CLP-induced inflammatory response and worsened the animal's survival. In contrast, pharmacological inhibition of Fabp4 markedly alleviated the CLP responsive inflammation and tissue damage and improved survival. We conclude that FABP4 is an important mediator of the sepsis response. Early intervention by pharmacological inhibition of FABP4 may help to manage sepsis in the clinic.